Analyses of the poultry value chain and its linkages and interactions with HPAI risk factors in Nigeria - Akinwumi, J.A.; Okike, Iheanacho; Bett, Bernard K.; Randolph, Thomas F.; Rich, Karl M. (International Food Policy Research Institute, 2009)
Highly pathogenic avian influenza (HPAI) has impacts that reverberate throughout the poultry marketing chain. Nigeria suffered waves of HPAI outbreaks that peaked twice in February 2006 and February 2007. The outbreaks affected 3,057 commercial and rural household farms causing 1.3 million of the country’s 160 million poultry to be destroyed at the cost of United States Dollars (USD) 5.4 m paid in compensation by the Government of Nigeria (Federal Department of Livestock [FDL], 2008). However, some impacts of HPAI are often overlooked in policy circles, with policymakers focusing mainly on the upstream impacts at the producer level. The cumulative downstream impacts of HPAI on traders, slaughterhouses, retailers, casual employment, and support services can often dwarf the impacts of the disease at the farm level. More significantly, the failure to capture these diverse impacts may have important implications on the evolution and control of disease that may accentuate its impact. In particular, socio-economic linkages embedded in livestock value chains may serve as important risk factors for the entry, spread, and persistence of disease. Thus, an understanding of these linkages is critical to inform policy and understand the broader livelihood impacts of disease.